EDUKASI PENULARAN DAN PENCEGAHAN PENYEBARAN COVID-19 PADA MASA PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) BERBASIS MIKRO DI DESA WISATA TEMPOS KABUPATEN LOMBOK BARAT - Nia Kurniati; Syaumudinsyah; Mey Susanti AS; Dewi Rispawati; Basuki Srihermanto (Nusantara Hasana Journal, 2021)
The COVID-19 pandemic is still a threat to all countries, including Indonesia. Various efforts have been made to control its spread. The implementation of micro-based Community Activity Restrictions (PPKM) is one of the Government's efforts to control the spread of COVID-19. The micro-based PPKM is implemented by the Government, because the number of COVID-19 cases continues to increase in various regions, including West Lombok Regency, NTB Province. The purpose of this community service activity is to provide education about the transmission and prevention of the spread of COVID-19, due to decreased public awareness in implementing health protocols. This activity was carried out in Tempos Tourism Village. The activity stage is the preparation stage, the activity implementation stage, and the reporting stage. At the implementation stage, education was provided about COVID-19 and also the distribution of masks to visitors. The result of this activity is that through education on the transmission of COVID-19 during the micro PPKM period, visitors understand the rules that apply during the micro PPKM period and also the implementation of the 6M health protocol, namely wearing masks, washing hands, keeping distance, reducing travel, increasing immunity and obeying the rules.